Analisis Pengaruh Celebrity Endorse, Beauty Vlogger, Word Of Mouth, Dan Brand Image Terhadap Minat Beli Produk Emina - Astuti, Sekar Meilana Kinanthi; Lukitaningsih, Ambar; Hatmanti, Lusia Tria (Jurnal Ilmiah Manajemen Kesatuan, 2021)
This study aims to determine the effect of Celebrity Endorse, Beauty Vlogger, Word Of Mouth and Brand Image on Purchase Intention for Emina Cosmetics products. This research is a quantitative research. The object of this research is the people of Yogyakarta City. The population of this study was 140 respondents. This research data obtained from individuals, by filling out a questionnaire. To find out the results of this study, researchers used validity tests, reliability tests, classical assumption tests, and multiple regression analysis and hypothesis testing. The results of data analysis with a significance of 0.05 show that the variables Celebrity Endorse and Beauty Vlogger have no significant effect on Purchase Intention, while the Word of Mouth and Brand Image variables have a significant effect on Purchase Intention. Keywords: Celebrity Endorse, Beauty Vlogger, Word of Mouth, Brand Image